Una coyuntura que conmocionó a Colombia : el conflicto con el Perú. Percepciones en el archivo de Carlos E. Restrepo (1932-1934) (2017)
ABSTRACT: These lines give a clear look at a significant historical conjuncture in the sphere of international relations, the definition of Colombian nationality and nationalism: the Colombo-Peruvian Conflict –and its aftermaths– between 1932 and 1934. Given the political ascendancy and the level of relationships of Carlos E. Restrepo, former Colombian president and recognized business and intellectual leader at that time, his correspondence registers a wide range of perceptions –of decision-making circles and people of the common–, that reflect a spontaneous collective feeling of rejection against the eventual loss of national sovereignty over vast border territories.